2018
DOI: 10.1371/journal.pone.0190837
|View full text |Cite
|
Sign up to set email alerts
|

Does ambient noise or hypobaric atmosphere influence olfactory and gustatory function?

Abstract: Multidimensional food perception is based mainly on gustatory and olfactory function. Recent research has demonstrated that hypobaric pressure impairs gustatory function and that background noise or distracting auditory stimulation impairs olfactory function. Using a hypobaric chamber, the odor identification, discrimination, and thresholds as well as taste identification and threshold scores were measured in 16 healthy male volunteers under normal and hypobaric (6380 ft) conditions using clinically validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…While complaints about noise in restaurants and bars would appear to have been on the rise in the west in recent years (e.g., Belluz, 2018;Moir, 2015; see Spence, 2014a, for a review), it is worth noting that researchers have actually been commenting on overly loud restaurants for many decades now (see Pettit, 1958, for an early example). The research that has been published to date shows that loud background noise, regardless of whether it is airplane noise, white noise, or even the background noise of a restaurant, or bar, affects both the perceived taste of food and drink, as well as people's ability to discriminate various aspects of their tasting experience (Rahne, Köppke, Nehring, Plontke, & Fischer, 2018;Trautmann, Meier-Dinkel, Gertheiss, & Mörlein, 2017; see Spence, 2014a, for a review).…”
Section: Background Noise and Its Impact On Tastingmentioning
confidence: 99%
“…While complaints about noise in restaurants and bars would appear to have been on the rise in the west in recent years (e.g., Belluz, 2018;Moir, 2015; see Spence, 2014a, for a review), it is worth noting that researchers have actually been commenting on overly loud restaurants for many decades now (see Pettit, 1958, for an early example). The research that has been published to date shows that loud background noise, regardless of whether it is airplane noise, white noise, or even the background noise of a restaurant, or bar, affects both the perceived taste of food and drink, as well as people's ability to discriminate various aspects of their tasting experience (Rahne, Köppke, Nehring, Plontke, & Fischer, 2018;Trautmann, Meier-Dinkel, Gertheiss, & Mörlein, 2017; see Spence, 2014a, for a review).…”
Section: Background Noise and Its Impact On Tastingmentioning
confidence: 99%
“…Intriguingly, however, white noise impaired participants' sensitivity for detecting sour and enhanced sweet taste ratings, while having no effect on the perception of bitter or salty tastants. Furthermore, Rahne et al (2018) reported no effects on olfactory detection thresholds. It should be noted that the n-butanol used in these experiments is not a food odor and these nonfood odors may be perceived differently (Albrecht et al, 2009).…”
Section: Background Noise and Its Influence On Taste/flavor Perceptionmentioning
confidence: 96%
“…(2011) reported higher taste and odor thresholds at low atmospheric pressure and noise compared to subsequently applied normal pressure. Rahne, Köppke, Nehring, Plontke, and Fischer (2018) have also recently published research in the area of background noise. They assessed both taste (gustatory) and orthonasal olfactory detection thresholds as a function of varying ambient noise (present vs. absent) and atmosphere (normal vs. hypobaric).…”
Section: Auditory Contributions To Flavor Perception In Spacementioning
confidence: 99%
“…However, pressure could have influenced the separate taste modalities, like 'salty'. Rahne et al [18] reported that hypobaric pressure significantly reduced the scores for 'sour' and 'salty' compared to the scores for 'sweet' and 'bitter'. O'Reilly et al [10] found an increase in 'sweet' sensitivity and a decline in 'sour' sensitivity after a 17-day dive.…”
Section: Gustationmentioning
confidence: 99%